The Dark Triad Traits and the Prediction of Eudaimonic Wellbeing - Liu, Yaqian; Zhao, Na; Ma, Min (Frontiers in Psychology, 2021)
Although numerous studies have focused on personality traits related to well-being, the relationship between the Dark Triad Traits and eudaimonic well-being is still unclear. The purpose of the present study was to explore how the Dark Triad Traits (i.e., narcissism, Machiavellianism, and psychopathy) affect eudaimonic well-being. Further, this study also aimed to explore the mediation effect of family support and hedonic wellbeing. The results showed that the present model had a good model fit (χ2/df = 1.91, p < 0.001, comparative-fit-index (CFI) = 0.96, tucker-lewis-index (TLI) = 0.95, root mean square error of approximation (RMSEA) = 0.04, standardized root mean square residual (SRMR) = 0.04). There is a significant association between the Dark Triad Traits and eudaimonic wellbeing. Specifically, narcissism directly predicts eudaimonic wellbeing, while the effects of Machiavellianism and psychopathy on eudaimonic wellbeing are serial two-mediator models, which are mediated by family support and hedonic wellbeing. The results would enrich theoretical studies on personality while providing some practical evidence on how to improve the subjective well-being of individuals.